2022
DOI: 10.3390/nano12244468
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Zirconium Magnetic Nanocomposite as a Bioactive Agent and Green Catalyst in the Four-Component Synthesis of a Novel Multi-Ring Compound Containing Pyrazole Derivatives

Abstract: New nanocomposites containing zirconium were synthesized using microwave irradiation. Their structure was confirmed by vibrating sample magnetometer (VSM) curves, X-ray diffraction (XRD) patterns, scanning electron microscope (SEM) and transmission electron microscopy (TEM) images, Fourier transform infrared spectroscopy (FT-IR), and Brunauer–Emmett–Teller (BET) N2 adsorption/desorption isotherms. After the structure confirmation of the zirconium magnetic nanocomposite, the catalytic properties in the synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Figure 3 shows the N 2 adsorption/desorption of coppercontaining MOF nanostructures A), cobalt-containing MOF nanostructures B), Cu/Co-hybrid MOF nanostructures C), and Cu/Co-hybrid MOF/PVA fiber nanostructures D). As can be seen, classical isotherms of all compounds were similar to the fourth type (Asiri et al, 2022) Frontiers in Materials frontiersin.org…”
Section: Cytotoxicity Activitymentioning
confidence: 54%
“…Figure 3 shows the N 2 adsorption/desorption of coppercontaining MOF nanostructures A), cobalt-containing MOF nanostructures B), Cu/Co-hybrid MOF nanostructures C), and Cu/Co-hybrid MOF/PVA fiber nanostructures D). As can be seen, classical isotherms of all compounds were similar to the fourth type (Asiri et al, 2022) Frontiers in Materials frontiersin.org…”
Section: Cytotoxicity Activitymentioning
confidence: 54%
“…Comparing the effects of Cu/DPA-MOF and Cu/DPA-MOF/OP/CS hydrogel shows that the Cu/DPA-MOF/OP/CS hydrogel was relatively more effective than Cu/DPA-MOF. The reason can be attributed to the specific surface area, and as mentioned, a higher specific surface area causes more effectiveness and efficiency in nanoparticles ( Asiri et al, 2022 ; Suksatan et al, 2022 ; Zeraati et al, 2022 ).…”
Section: Resultsmentioning
confidence: 97%
“…Based on the BET results, the specific surface area for Cu/DPA-MOF and Cu/DPA-MOF/OP/CS hydrogel was obtained as 28.200 m 2 /g and 37.700 m 2 /g, respectively. Based on previous studies, the high specific surface area is an essential factor in the reactivity, properties, and performance of nanoparticles ( Asiri et al, 2022 ; Zeraati et al, 2022 ). Therefore, it can be suggested that the polymerization of Cu/DPA-MOF Cu/DPA by oxidized pectin and chitosan caused a significant increase in the specific surface area.…”
Section: Resultsmentioning
confidence: 99%
“…The FT-IR spectrum of the synthesized Cu-MOF and penicillinoate@Cu-MOF showed peaks related to Cu-O, C=N, C=C, and C-H at 508 cm −1 ( Elango et al, 2018 ), 1,489 cm −1 ( Abdtawfeeq et al, 2022 ), and 1,535 cm −1 ( Asiri et al, 2022 ), respectively. As can be seen from the comparison in Figure 5 , in the FT-IR spectrum of penicillinoate@Cu-MOF, the peaks corresponding to C-S, aliphatic ketones, and beta-lactam C=O were observed at 790 cm −1 ( Bastian Jr and Martin, 1973 ; Bayati and Wei, 2014 ; Moghaddam-Manesh et al, 2020b ), 1722 cm −1 ( Bayati and Wei, 2014 ), and 1747 cm −1 ( Thumanu et al, 2006 ; Esmaeilpour et al, 2016 ; Al-Adhami et al, 2020 ), respectively.…”
Section: Resultsmentioning
confidence: 99%